Prevalence of Oral Cancer in Western Population of Maharashtra for 3 Years: A Prospective Study - Abhishek Anilrao Gole; S R Ashwinirani; Vidya Kadashetti; Girish Suragimath; Shrutika Muneshwar; Priti Godse (Wolters Kluwer Medknow Publications, 2023)
Introduction: In developing countries, oral cancer (OC) is estimated to be the third most common malignancy after cancer of the cervix and stomach. The aim of this study was to report the prevalence of OC for 3 years and its association with age, gender, type, and duration of habits along with the site of OC. Materials and Methods: This study was conducted in the Department of Oral Medicine and Radiology from January 2019 to December 2021. All the patients were examined after recording their demographic data using a mouth mirror and probe. The diagnosis of OC was arrived based on the clinical features of the lesions. The type and duration of habits and site were recorded in clinical pro forma. The Statistical Package for the Social Sciences (SPSS) software version 21.0 was used for the statistical analysis, the Chi-square test was applied, and the significance level was set at P < 0.05. Results: The prevalence of OC was 0.22% in our study. Of 317 cases, the majority of the patients were males (n = 204), and females (n = 113) accounted for a male: female ratio of 2:1. The most common age affected was 51-70 years with a history of tobacco chewing, followed by patients with multiple habits (smokers, tobacco chewers, and alcoholic). The buccal mucosa was the most common site followed by malignancies of multiple sites. Conclusion: Regular camps regarding tobacco cessation and counseling should be taken care of by dentists. Male patients aged above 40 years are routinely recommended for dental visits.